Mechanisms associated with the synergistic induction of resistance to tobacco black shank in tobacco by arbuscular mycorrhizal fungi and β-aminobutyric acid - Li, Jia; Cai, Bo; Chang, Sheng; Yang, Ying; Zi, Shuhui; Liu, Tao (Frontiers in Plant Science, 2023)
Tobacco black shank (TBS), caused by Phytophthora nicotianae, is one of the most harmful diseases of tobacco. There are many studies have examined the mechanism underlying the induction of disease resistance by arbuscular mycorrhizal fungi (AMF) and β-aminobutyric acid (BABA) alone, but the synergistic effects of AMF and BABA on disease resistance have not yet been studied. This study examined the synergistic effects of BABA application and AMF inoculation on the immune response to TBS in tobacco. The results showed that spraying BABA on leaves could increase the colonization rate of AMF, the disease index of tobacco infected by P.nicotianae treated with AMF and BABA was lower than that of P.nicotianae alone. The control effect of AMF and BABA on tobacco infected by P.nicotianae was higher than that of AMF or BABA and P.nicotianae alone. Joint application of AMF and BABA significantly increased the content of N, P, and K in the leaves and roots, in the joint AMF and BABA treatment than in the sole P. nicotianae treatment. The dry weight of plants treated with AMF and BABA was 22.3 % higher than that treated with P.nicotianae alone. In comparison to P. nicotianae alone, the combination treatment with AMF and BABA had increased Pn, Gs, Tr, and root activity, while P. nicotianae alone had reduced Ci, H2O2 content, and MDA levels. SOD, POD, CAT, APX, and Ph activity and expression levels were increased under the combined treatment of AMF and BABA than in P.nicotianae alone. In comparison to the treatment of P.nicotianae alone, the combined use of AMF and BABA increased the accumulation of GSH, proline, total phenols, and flavonoids. Therefore, the joint application of AMF and BABA can enhance the TBS resistance of tobacco plants to a greater degree than the application of either AMF or BABA alone. In summary, the application of defense-related amino acids, combined with inoculation with AMF, significantly promoted immune responses in tobacco. Our findings provide new insights that will aid the development and use of green disease control agents.